Electrochemistry of solvated proton in dimethylsulphoxide : II. Kinetics and mechanism of the electrolytic evolution of hydrogen on iron - Posadas, Dionisio (1970)
The kinetics of the electrolytic evolution of hydrogen on iron electrodes using solutions of HCl in DMSO has been investigated. The electrode reaction was studied within the temperature range from 20 to 45°C at various HCl concentrations, in the presence of an excess of potassium perchlorate. The mechanism interpreting the electrode reaction comprises as first step the simple solvated-hydrogen-ion discharge as rate-controlling followed probably by a hydrogen adatom combination process. The theoretical parameters derived from this mechanism coincide with the results obtained from steady as well as from non-steady measurements.